The effects of covid-19 on the cost of international sea freight - Chiscul Padilla, Miguel Angel (2022)
This article deals with the effects caused by the covid-19 pandemic on the cost of international sea freight due to its excessive increase in its price, which is reflected in the costs of the products or supplies required by the different markets with the objective of satisfying their needs, since a series of circumstances have occurred that have caused international maritime freight to become more expensive, bringing as a domino effect that the value of merchandise in customs reflects said increase and therefore a greater tax burden, motivating make products even more expensive, making them inaccessible to the low-income population who urgently demand food, medicine and technology products. China is the main supplier of a large part of the products demanded by the world and therefore the one that requires a greater number of containers, however, in the face of thecovid-19 pandemic, security protocols have been taken in order to avoid contagion. However, the coronavirus has been detected in the shipments, generating contagion in the customs personnel, due to this, sanitary and customs controls have increased more, generating a slowness in the clearance of shipments, as well as that a large part of the containers deployed throughout the planet they do not return in the same quantity due to the government measures that each nation has adopted in order to safeguard health and prevent the spread of contagion.